The Urgency and Implication of Breast Milk Donor in Indonesia in Mashlahah Perspective - Khotifatul Defi Nofitasari (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2021)
In Islamic teachings, the issue of breastfeeding is a very important issue to pay attention to, because it can have an impact on the issue of the prohibition of marriage and lineage. The purpose of this study is to dig deeper into the urgency of breastfeeding donors and their implications based on the practice of breastfeeding donors in Indonesia, and a review of the mashlahah of these breast milk donors. T his type of research is library research, with analytical descriptive method. This research uses mashlahah theory with ushul fiqh approach. As a result, breast milk donation in Indonesia can be done by fulfilling several conditions: first, the request of the biological mother or the baby’s family. Second, the identity, religion, and address of the breast milk donor are clearly known by the mother or family of the baby receiving the donor. Third, the approval of the breast milk donor by knowing the identity of the donor recipient baby. Fourth, the breast milk donor is in good health and has no medical indication. Fifth, breast milk is not traded. Meanwhile, based on Ijtihâd istishlâhî, breast milk donation which aims to help babies who do not get breast milk from their biological mothers for certain reasons, is a humanitarian aid to save human life. Therefore, it is legally permissible to donate breast milk and can be categorized as mashlahah dharuriyat if the mother of the baby is sick and the baby is premature or sick. Including mashlahah hajiyat if the baby’s mother dies, or her whereabouts are not known..